Financial Markets and the Transition to a Low-Carbon Economy: Challenging the Dominant Logics. (March 2019) - Louche, Celine; Busch, Timo; Crifo, Patricia; Marcus, Alfred
Financial markets play a major role in contributing to the transition to a low-carbon economy. Although many initiatives and developments are taking place, this is just the beginning. In this article, we argue for a theory of change—a theory rooted in logics that will help financial markets play a key role in the transition to a low-carbon economy. We argue that the current dominant logics in finance—short-termism, predictability of the future based on ex-post data, price efficiency, and risk-adjusted returns—impede the effective integration of climate considerations in financial markets. We suggest four alternative logics that can enable and foster a change toward the low-carbon economy: long-termism, systems interconnectedness, carbon price dynamics, and active ownership.